Surgical outcomes in gastroenterological surgery in Japan: Report of the National Clinical Database 2011‐2018. Issue 3 (20th March 2020) - Kakeji, Yoshihiro; Takahashi, Arata; Hasegawa, Hiroshi; Ueno, Hideki; Eguchi, Susumu; Endo, Itaru; Sasaki, Akira; Takiguchi, Shuji; Takeuchi, Hiroya; Hashimoto, Masaji; Horiguchi, Akihiko; Masaki, Tadahiko; et al.
Abstract: The National Clinical Database (NCD) of Japan grew rapidly, harvesting over 11 million cases of data between 2011 and 2018 from more than 5000 facilities. This is the Report of the NCD based upon gastrointestinal surgery information in 4 420 175 cases from 2011 to 2018. More than 70% of all gastrointestinal surgeries were performed at certified institutions, and the percentage of surgeries performed at certified institutions was particularly high for the esophagus (93.8% in 2018), liver (89.4%), pancreas (91.3%), and spleen (86.9%). Also, more than 70% of the surgeries were performed with the participation of the board‐certified surgeon. As the patients have been getting older, the morbidities have been increasing. However, the mortalities have been kept at a low level. The rates of endoscopic surgery have been increasing year by year, especially high in low anterior resection (67.0%) and esophagectomy (61.0%). Nationwide, this database is surely expecting to ensure the quality of board certification system and surgical outcomes in gastroenterological surgery. Abstract : This is the Report of the National Clinical Database (NCD) based upon gastrointestinal surgery information in 4 420 175 cases from 2011 to 2018. Nationwide this database is surely expecting to ensure the quality of the board certification system and surgical outcomes in gastroenterological surgery.